Effect of the Exercise Dance for Seniors (EXDASE) program on lower-body functioning among institutionalized older adults - Holmerová, Iva; Macháčová, Kateřina; Vaňková, Hana; Veleta, Petr; Jurašková, Božena; Hrnčiariková, Dana; Volicer, Ladislav; Andel, Ross (Journal of aging and health, 2010)
OBJECTIVE: The authors conducted a randomized control trial to examine the effect of the Exercise Dance for Seniors (EXDASE) program on lower-body functioning among older individuals from residential care facilities in the Czech Republic. METHOD: Participants were randomly assigned into an experimental or control group. The experimental group completed a 3-month EXDASE program. Lower-body functioning was assessed using four performance-based measures. A 2 (group) x 2 (test) general linear model for repeated measures was used to explore whether differences in performance could be attributed to the intervention. RESULTS: The authors found Group x Test interactions for the chair stand test, F(1, 50) = 14.37, p < .001, the 2-minute step test, F(1, 50) = 7.33, p = .009, the chair sit-and-reach test, F(1, 50) = 5.28, p = .026, and the timed up-and-go test, F (1, 44) = 6.59, p = .014, indicating that the experimental group outperformed the control group from pretest to posttest. DISCUSSION: A relatively simple dance-based exercise can support lower-body functioning in previously sedentary, frail older adults.
Keywords: Program Evaluation; bérec; křehký senior; Humans; Residential Facilities; tanec; Female; Aged; Exercise Therapy; výsledek terapie; senioři; lidé; ženské pohlaví; Male; ubytovací zařízení; Treatment Outcome; Czech Republic; Aged, 80 and over; Frail Elderly; senioři nad 80 let; hodnocení programu; Česká republika; mužské pohlaví; terapie cvičením; Dancing; Leg